An oriented coincidence index for nonlinear Fredholm inclusions with nonconvex-valued perturbations (Abstract and Applied Analysis)
We suggest the construction of an oriented coincidence index for nonlinear Fredholm operators of zero index and approximable multivalued maps of compact and condensing type. We describe the main properties of this characteristic, including applications to coincidence points. An example arising in the study of a mixed system, consisting of a first-order implicit differential equation and a differential inclusion, is given.